Antiretroviral adherence for adolescents growing up with HIV: understanding real life, drug delivery and forgiveness. (May 2020) - Foster, Caroline; Ayers, Sara; Fidler, Sarah
Poorer adherence to medication is normal in adolescence and is one of a range of risk-taking behaviours common during a developmental stage that encompasses enormous cognitive, physical, sexual, social and emotional change. For adolescents living with human immunodeficiency virus (HIV) infection, poor adherence to antiretroviral therapy (ART) confers two significant challenges: poor health, but also the specific additional burden of onward transmission to partners. Late adolescence (15–19 years) is the only age group where HIV-associated mortality is rising, driven by poor adherence to ART and lack of access to second-line therapy, particularly amongst surviving perinatally infected young people. A previous lack of well-powered randomised multimodal behavioural ART adherence interventions specifically targeting adolescents is now being addressed and ongoing studies registered to ClinicalTrials.gov are described in the context of previous data. Accepting that despite enhanced support, some adolescents will continue to struggle with adherence, we must address how best to use existing ART agents to reduce mortality and allow adolescents the time to mature into adult life. Single-tablet regimens with a high genetic barrier to resistance based on integrase inhibitors and boosted protease inhibitors exist, but global access, in resource limited settings of young people living with HIV reside, is limited. Pragmatically, such regimens tolerate the intermittent adherence so characteristic of adolescence, preserving immune function, without the rapid evolution of resistance. The potential role of long-acting injectable ART, specifically cabotegravir and rilpivirine, is discussed and future strategies including ultra-long-acting drug-delivery systems and broadly neutralising monoclonal antibodies explored.